2011
DOI: 10.1080/07366299.2011.539145
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the use ofN,N,N′,N′-Tetra(2-Ethylhexyl) Diglycolamide (TEHDGA) for Actinide Partitioning II: Investigation on Radiolytic Stability

Abstract: N,N,N ,N -tetra(2-ethylhexyl)diglycolamide (TEHDGA) was found to be a promising extractant for actinide partitioning from high-level waste (HLW) (Part I). In order to evaluate the applicability of TEHDGA to the HLW partitioning process, investigations on its radiolytic stability were carried out. The present work deals with the studies on the uptake of americium by γ -irradiated 0.2 M TEHDGA/n-dodecane in the absence and presence of phase modifiers-di(n-hexyl)octanamide (DHOA), isodecanol and n-decanol-against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…[15] In further study of the radiolysis of T(EH)DGA, Deepika et al found that D Am values decreased more for T(EH)DGA when irradiated in the presence of the n-dodecane and HNO 3 . [4] However, these authors did not attempt to separate the effects of the diluent and the aqueous phase and erroneously concluded that nitric acid enhanced T(EH)DGA decomposition, rather than to electron transfer Downloaded by [New York University] at 23:55 14 June 2015 reactions with the n-dodecane radical cation. Thus, contradictory reports have appeared in the literature, possibly confounded by the use of the various phase modifiers.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[15] In further study of the radiolysis of T(EH)DGA, Deepika et al found that D Am values decreased more for T(EH)DGA when irradiated in the presence of the n-dodecane and HNO 3 . [4] However, these authors did not attempt to separate the effects of the diluent and the aqueous phase and erroneously concluded that nitric acid enhanced T(EH)DGA decomposition, rather than to electron transfer Downloaded by [New York University] at 23:55 14 June 2015 reactions with the n-dodecane radical cation. Thus, contradictory reports have appeared in the literature, possibly confounded by the use of the various phase modifiers.…”
Section: Introductionmentioning
confidence: 98%
“…1b) has been promoted as a cheaper alternative with less affinity for fission product complexation. [4] The weaker complexing ability of T(EH)DGA was used to advantage by Lumetta et al [5] in the design of the ALSEP (Actinide Lanthanide SEParation) solvent, where, in combination with the acidic soft-donor ligand diethylenetriamine pentaacetic acid (DTPA), it was used to give a single extraction/strip cycle separation of the actinides from the lanthanides. [5,6] A loaded organic phase consisting of 0.05 M T(EH)DGA and 0.75 M 2-ethylhexylphosphonic acid mono-2-ethylhexyl ester (HEH[EHP]) in n-dodecane, when stripped with an aqueous phase consisting of 0.01 M DTPA and 0.2 M citric acid, provided α Nd/Am values in the range 10-30.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to mention here that some of the degradation products can interfere in the performance of the extraction system which is reflected in poor decontamination. Deepika, et al, reported both GC-MS as well as IR spectroscopic analysis of T2EHDGA [23]. We have tried to analyze the FT-IR spectra of the diglycolamide extractants, both unirradiated and exposed to 1000 kGy (Supporting information).…”
Section: Gc-ms Studies Of the Irradiated Trdga Samplesmentioning
confidence: 99%
“…There are several reports on the radiolytic stability of diglycolamide extractants, particularly TODGA and T2EHDGA ( , , , -tetra-2-ethylhexyl diglycolamide) [17][18][19][20][21][22][23]. Radiolytic stability of TODGA was studied by Sugo and et al and the G-value (number of molecules undergo degradation after absorption of 100 eV of energy) for TODGA was found to be 8.5±0.6 molecules/100 eV [17].…”
Section: Introductionmentioning
confidence: 98%
“…The decrease in the transport rate was found to be lower for the solvent containing higher concentration of DHOA. This is due to the fact that amides such as DOHA (N,N,-di-n-octyl hexanamide, which is similar to DHOA) inhibits the radiolysis of TODGA [8] and DHOA has been reported to inhibit radiolysis of T2EHDGA (tetra-N,N,N ,N -2-ethylhexyldiglycolamide [24], which is analogous to TODGA). As a result, when 0.1 M TODGA in n-dodecane was irradiated at 100 MRad, ∼79% Am(III) got transported in ∼5 h. In sharp contrast, the transport of Am(III) increased to ∼85% under identical conditions when 0.1 M TODGA + 0.5 M DHOA in n-dodecane was used as the carrier solvent.…”
Section: Am(iii) Transportmentioning
confidence: 99%